2006
DOI: 10.1016/j.schres.2006.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive and social cognitive correlates of formal thought disorder in schizophrenia patients

Abstract: The neurocognitive and social cognitive correlates of two types of formal thought disorder (i.e., bizarre-idiosyncratic and concrete thinking) were examined in 47 stable outpatients with schizophrenia. Both types of thinking disturbance were related to impairments in verbal learning, intrusions in verbal memory, immediate auditory memory, sustained attention, and social schema knowledge. Distractibility during an immediate memory task was associated with more frequent bizarre verbalizations but not concretenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 51 publications
5
35
0
2
Order By: Relevance
“…FTDs have been found to be related to several cognitive dysfunctions in schizophrenia, such as impairments in attention, information processing, working memory, discourse planning semantic processing, and executive dysfunction 17,20,[44][45][46] ; and it seems these deficits in attention and information processing may be part of what causes FTDs. Furthermore, disorganization and negative syndromes were both significantly associated with impairments in executive function 47,48 though showing different patterns of association with different executive tests.…”
Section: Attentional Impairment and Ftdmentioning
confidence: 99%
“…FTDs have been found to be related to several cognitive dysfunctions in schizophrenia, such as impairments in attention, information processing, working memory, discourse planning semantic processing, and executive dysfunction 17,20,[44][45][46] ; and it seems these deficits in attention and information processing may be part of what causes FTDs. Furthermore, disorganization and negative syndromes were both significantly associated with impairments in executive function 47,48 though showing different patterns of association with different executive tests.…”
Section: Attentional Impairment and Ftdmentioning
confidence: 99%
“…Language disorganization is an observable expression of formal thought disorder (FTD) that has been strongly associated with clinical expression and broader neurocognitive deficits in psychotic disorders, including schizophrenia-spectrum disorders (Kerns and Berenbaum, 2002;Subotnik et al, 2006;Ceccherini-Nelli et al, 2007). Previous studies have demonstrated a close association between FTD and other symptomotology in schizophrenia-spectrum disorders, such as delusions and hallucinations, (Andreasen and Grove, 1986;Harrow and Marengo, 1986;Kimhy et al, 2005;Strik et al, 2008), implicating it as a clinical indicator of acute psychotic states.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the novel exploration of the relationship between thought disorder and affect in schizophrenia-spectrum disorders, the current study also supports work that formulates thought disorder as a form of cognitive dysfunction; significant relationships have been shown for measures of working memory (Docherty, 2005;Docherty, Hall, & Gordinier, & Cutting, 2000;Docherty et al, 1996b;Docherty, Strauss, Dinzeo, & StHilaire, 2006;Kearns, 2007;Stirling, Hellewell, Blakey, Deakin, 2006); attention (Docherty, 2005;Docherty et al, 2000;Docherty et al, 1996b;Docherty et al, 2006;Subotnik et al, 2006); fluency (Docherty et al, 1996b;Stirling et al, 2006), memory (Docherty et al, 2000;Subotnik et al, 2006), and nonverbal sorting ability (Harrow et al, 2003). Moreover, both cognitive dysfunction and thought disorder are both early symptoms of the illness that often remain stable and intractable despite antipsychotic medication (Goldberg & Green, 1995).…”
Section: Discussionsupporting
confidence: 77%